Visual-Evoked-Response-Supported Outcome of Intravitreal Erythropoietin in Management of Indirect Traumatic Optic Neuropathy - Mohammad Ahmad Rashad; Ahmed Abdel Meguid Abdel Latif; Hazem A. Mostafa; Samah Mahmoud Fawzy; Mahmoud Abdel Meguid Abdel Latif (Journal of Ophthalmology)
Purpose. Investigating the efficacy of intravitreal injection of erythropoietin (EPO) in managing indirect traumatic optic neuropathy (ITON) of different durations. Methods. A case series that included two groups of ITON patients: recent ITON group (<3 months trauma duration; 7 eyes) and old duration ITON group (3–36 months; 7 eyes). Diagnostic computerized tomography (CT) and baseline flash visual evoked response (VER) were performed at the presentation time. At the initial visit and each follow-up, all patients had undergone assessment of best-corrected visual acuity (BCVA), pupil reaction, and anterior and posterior segments. VER was repeated 1 and 3 months after injection. All patients received an intravitreal injection of 2000 IU EPO in 0.2 ml of commercially available sterile EPREX 4000 solution, Jansen Cilag, Zug, Switzerland. Five patients had received a second injection 3 months later. Results. Significant improvement was found in BCVA, VER amplitude, and latency (P<0.0001, 0.0154, and 0.0291, respectively). Initial values of BCVA, VER amplitude, and latency correlated significantly to the final values. Differences between recent and old trauma groups were insignificant in the three parameters. In patients who received second injection, further clinical but statistically insignificant improvement was noted in BCVA in 60% of patients, VER amplitude in 50% of patients, and in VER latency in 100% of patients. No complications were recorded. Conclusion. Intravitreal injection of EPO may be effective and safe in treatment of recent and old indirect traumatic optic neuropathy.